2022
DOI: 10.3390/genes13112040
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Molecular Responses of Barley Genotypes to Salinity Stress

Abstract: Among cereals, barley is tolerant to high levels of salinity stress; however, its performance and global production are still dramatically affected by salinity. In this study, we evaluated the behavior of a set of advanced genotypes of barley with aim of assessing the physiological and molecular mechanisms involved in salinity tolerance. The experiment was conducted using a hydroponic system at optimal growing temperature and photoperiod conditions. The results of the analysis of variance (ANOVA) showed signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…As a result, it enables the assessment of salt tolerance in genotypes by considering all the examined traits. Additionally, it assists in identifying the most influential trait that contributes the most to the overall variance and effectively distinguishes between salt-tolerant and sensitive genotypes [9,50,51]. The PCA results in this study successfully identified the screening criteria that effectively evaluate the salt tolerance of wheat genotypes under real field conditions.…”
Section: Discussionmentioning
confidence: 84%
“…As a result, it enables the assessment of salt tolerance in genotypes by considering all the examined traits. Additionally, it assists in identifying the most influential trait that contributes the most to the overall variance and effectively distinguishes between salt-tolerant and sensitive genotypes [9,50,51]. The PCA results in this study successfully identified the screening criteria that effectively evaluate the salt tolerance of wheat genotypes under real field conditions.…”
Section: Discussionmentioning
confidence: 84%
“…Barley, as one of the most salt‐tolerant cereals, may be a pioneer in shifting crop production to saline lands. Therefore, much attention has been paid to breeding and deciphering the underlying mechanism of salt‐tolerant barley varieties (Gupta et al, 2022; Hura, 2020; Jadidi et al, 2022; Jiang et al, 2022; Munns & Tester, 2008). After growing in the solution or sand culture containing NaCl for 3 weeks, barley showed a higher increase of the shoot dry matter than other cereals, including rice ( Oryza sativa ), durum wheat ( Triticum turgidum ssp durum ), and bread wheat ( Triticum aestivum ) (Munns & Tester, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…When the osmotic pressure within the cells falls, guard cell water outflow will result in stoma closure and the contraction of guard cells (Liu et al). This often results in salt stress leaves having higher Na + and Cl contents, lower K + contents, and eventually closing their stomas (Jadidi et al, 2022). The reduced stoma opening significantly decreases the intercellular CO2 concentration and photosynthetic rate, as well as CO2 diffusion from the environment to the chloroplast (Zou et al, 2022).…”
Section: Osmotic Pressure Affected By Salinitymentioning
confidence: 99%